Cannabinoid Hyperemesis Syndrome: Case Report of a Paradoxical Reaction with Heavy Marijuana Use. (28th May 2012) - Cox, Benjamin; Chhabra, Akansha; Adler, Michael; Simmons, Justin; Randlett, Diana
Abstract : Cannabinoid hyperemesis syndrome (CHS) is a rare constellation of clinical findings that includes a history of chronic heavy marijuana use, severe abdominal pain, unrelenting nausea, and intractable vomiting. A striking component of this history includes the use of hot showers or long baths that help to alleviate these symptoms. This is an underrecognized syndrome that can lead to expensive and unrevealing workups and can leave patients self-medicating their nausea and vomiting with the very substance that is causing their symptoms. Long-term treatment of CHS is abstinence from marijuana use—but the acute symptomatic treatment of CHS has been a struggle for many clinicians. Many standard medications used for the symptomatic treatment of CHS (including ondansetron, promethazine, and morphine) have repeatedly been shown to be ineffective. Here we present the use of lorazepam as an agent that successfully and safely treats the tenacious symptoms of CHS. Additionally, we build upon existing hypotheses for the pathogenesis of CHS to try to explain why a substance that has been used for thousands of years is only now beginning to cause this paradoxical hyperemesis syndrome.